2016
DOI: 10.1016/j.physbeh.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Amylin-mediated control of glycemia, energy balance, and cognition

Abstract: Amylin, a peptide hormone produced in the pancreas and in the brain, has well-established physiological roles in glycemic regulation and energy balance control. It improves postprandial blood glucose levels by suppressing gastric emptying and glucagon secretion; these beneficial effects have led to the FDA-approved use of the amylin analog pramlintide in the treatment of diabetes mellitus. Amylin also acts centrally as a satiation signal, reducing food intake and body weight. The ability of amylin to promote n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 226 publications
(260 reference statements)
0
33
0
Order By: Relevance
“…Amylin receptors (AMYs) consist of dimerized calcitonin receptor (CTR) with receptor activity-modifying proteins (RAMPs) and belong to class B GPCR. Amylin, the endogenous peptide that binds to the amylin receptor, mediates glycemic regulation, control of energy balance, and cognitive processes and modulates innate immunity through regulatory T cells [ 16 18 ]. We have previously shown that the deleterious effects of Aβ on cultured human and rat neurons are expressed through the amylin receptor and that amylin receptor antagonists, such as AC253, are neuroprotective against Aβ toxicity [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amylin receptors (AMYs) consist of dimerized calcitonin receptor (CTR) with receptor activity-modifying proteins (RAMPs) and belong to class B GPCR. Amylin, the endogenous peptide that binds to the amylin receptor, mediates glycemic regulation, control of energy balance, and cognitive processes and modulates innate immunity through regulatory T cells [ 16 18 ]. We have previously shown that the deleterious effects of Aβ on cultured human and rat neurons are expressed through the amylin receptor and that amylin receptor antagonists, such as AC253, are neuroprotective against Aβ toxicity [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While higher levels of blood amylin are associated with higher BMI, lower blood levels of amylin have been observed in adults with more severe forms of cognitive impairment, such as dementia [18]. This is congruent with the low BMI and low leptin levels observed cross-sectionally in those with dementia, and that cognition is enhanced with the amylin analog, pramlintide [19]. Similar to other reports in HIV− samples that relate anthropometric measures to gut hormone levels, our findings demonstrate that higher amylin levels were associated with higher levels of overweight and obesity [53].…”
Section: Discussionmentioning
confidence: 83%
“…Amylin is best known as a glucoregulatory hormone that helps control glucose homeostasis through a variety of mechanisms including controlling gastric emptying, leading to reduced meal size and weight loss. There are several recent reviews on this topic, to which readers are referred for further information . In type I diabetes and in insulin‐requiring type II diabetes, there is an amylin deficit.…”
Section: Amylin Is a Glucoregulatory And Satiety Hormonementioning
confidence: 99%
“…CGRP is principally a neuropeptide, whereas the canonical role for amylin is as an endocrine hormone that signals to the brain and acts as a satiety factor. 2,[26][27][28] The major site of expression of amylin is in the b cells of the islets of Langerhans in the pancreas, although extra-pancreatic amylin expression has also been reported. Amylin likeimmunoreactivity has been reported in the stomach and in some neurons.…”
Section: Where Is Amylin Found?mentioning
confidence: 99%
See 1 more Smart Citation